EFEKTIVITAS DAN TINGKAT PARTISIPASI MASYARAKAT TERHADAP PROGRAM PENGENTASAN KEMISKINAN PERKOTAAN (P2KP) DI KOTA BANDAR LAMPUNG - Yanfika, Helvi (Jurnal AGRISEP, 2011)
The goal of provision of venture capital through P2KP is to improve the economy and provide infrastructure assistance to the urban poor in the form of concern that the government is "facilitating" the passage "public participation process". Purposes of this study are to determine the level of effectiveness, know the dynamics of group relationships, determine the relationship of program characteristics of community participation in the program, and determine the relationship at the level of stakeholder support for urban poverty eradication program (P2KP) in the city of Bandar Lampung. The research was conducted in the city of Bandar Lampung in July-October 2011. The sample in this study were drawn using simple random technique (simple random sampling), and the respondent sample was taken from the population of members of Self-Help Groups (SHGs) of poor city of Bandar Lampung group, in order to obtain a sample of 39 respondents. Data analyses in this study were tabulation and descriptive method. To test the hypothesis, non-parametric statistical test Spearman Rank correlation was used. The study results show that in general urban poverty eradication program (P2KP) in Bandar Lampung is in fairly good views. Assessment of the dynamics of the group (X1) is quite good most of the respondents are 53.85% in the medium category, and program characteristics (X2) was 71.79% which is good enough, as well as the support of stakeholders (X3) is 58.97%, and public participation (Y1) in the high category is 71.79%, indicating the effectiveness of programs in the city of Bandar Lampung P2KP pretty good, and the results of the analysis showed a significant relationship between the dynamics of the group, the characteristics of program with the participation of stakeholders support to the program in the city of Bandar Lampung P2KP with 99% confidence level. Keywords: Effectiveness, Participation, Poverty Eradication